Exploring the Causes, Prevalence and Socioeconomic Implications of Illegal Immigration in Northern Nigeria - Ojonugwa, Ameh Sunday; Jehu, Anande Terver (Darul Yasin Al Sys, 2025)
Illegal immigration remains a pressing concern in Northern Nigeria, driven by economic, political, social, and environmental factors. This study explores the causes, prevalence, and socioeconomic implications of illegal immigration in the region, highlighting its impact on labour markets, national security, social cohesion, and economic development. The study adopted the social conflict theory by Karl Marx as its theoretical framework. The research utilizes documentary evidence, analyzing existing reports, scholarly articles, and policy documents to provide a comprehensive understanding of migration trends and their consequences. Findings reveal that economic hardship, political instability, porous borders, and historical ethnic ties significantly contribute to irregular migration. Northern Nigeria serves as both a source and transit region, with migrants from neighboring countries such as Niger, Chad, and Cameroon entering the region for employment opportunities in agriculture, trade, and informal sectors. The prevalence of illegal immigration is exacerbated by weak border control mechanisms, corruption, and inadequate legal frameworks. The study further identifies key socioeconomic challenges, including job displacement, pressure on public services, security threats, and human rights violations. While illegal immigrants contribute to informal labor markets, their presence often leads to tensions with local populations and governance difficulties. The paper recommends strengthening border security, enhancing regional cooperation, creating legal migration pathways, and promoting economic development initiatives to address the root causes of migration. A holistic approach that balances enforcement with humanitarian considerations is essential for effective migration management. Future research should focus on data-driven policy interventions and cross-border collaborations to mitigate the adverse effects of illegal immigration while harnessing its potential benefits.